Digital game-based learning in mathematics learning with cultural contexts: A systematic literature review - Zea Zisman Usman; Nanang Priatna; Dadang Juandi; Trisonia Fitria (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2026)
The increasing integration of digital technologies into education has encouraged the use of Digital Game-Based Learning (DGBL) to enhance students’ engagement and mathematical understanding; however, research on incorporating cultural contexts into DGBL for mathematics learning remains fragmented and lacks a comprehensive synthesis. This study aims to systematically review existing literature on culturally contextualized DGBL in mathematics education by identifying dominant research designs, participant characteristics, mathematical content, cultural representations, learning outcomes, and future research directions. A systematic literature review was conducted following the PRISMA framework using data retrieved from the Scopus database with the keywords "digital game-based learning" AND "cultural" AND "mathematics". Of the 153 initially identified documents, 14 studies met the inclusion and quality assessment criteria and were analyzed through content analysis. The results of the study are the most widely used types of qualitative and experimental research, with the research subjects being elementary and junior high school students. The research instruments that are widely used are interviews, questionnaires, observations and tests. Mathematics material in elementary schools is widely used in this research, with the cultural context being the culture and identity of students. Most of the media used is digital games. Most studies reported positive effects on students’ attitudes, engagement, learning experiences, and learning processes. This review contributes a comprehensive overview of methodological and thematic trends in culturally contextualized DGBL research and highlights the need for theoretically grounded, culturally meaningful, and pedagogically robust game-based learning environments that support diverse learners and more advanced mathematical learning objectives.